Estudo eletroquímico de interação de Quinona de interesse biológico e Dendrímeros PAMAM de 2ª e 3ª geração - Candido, Anna Caroline Lima (2017)
β-lapachone (βLP) is a highly studied and promising plant-derived quinone in the treatment of cancer, but one of its characteristics limits its pharmacological properties, which is its low solubility in water. In the present study an alternative to increase the solubility of β-lapachone naphthoquinone with polyamidoamine dendrimer (PAMAM) of generation 2 and 3 (G2 and G3), Which is a highly branched and nanometer-sized polymer. Electrochemical techniques such as cyclic voltammetry were used, in protic media (phosphate pH 7.0) using glassy carbon as working electrode, while the counter electrode was a Pt wire and the reference electrode an Ag|AgCl|Cl− (saturated), using a Autolab PGSTAT12 potentiostat. All experiments were conducted at room temperature (25 ± 2 ºC) and purging an inert gas (Argon). Also complexes of βLP with PAMAM were prepared and characterized by spectroscopy techniques, as UV visible (UV-vis) and Infrared by Fourier Transform (FTIR). In the electrochemical studies, it was observed a better amount of current to BLP when it was analyzed electrode modified with carbon nanotube (CNT) and PAMAM G2 or G3 than when it was only with the CNT, indicating a higher interaction of this quinone with dendrimer. Varying the concentration of the βLP with CNT/PAMAM G2 or G3 electrode can calculate the constant of interaction between them (6,63x102 e 2,59x102). To have the most of active sites available of the dendrimer and propose how is this interaction, the PAMAM G2 was immobilized on the gold electrode with MUA and the concentration of the quinone was varied and the equilibrium constant of the calculated complex (2,9x104). Studies with the free PAMAM in solution were performed, in which increasing concentrations of PAMAM was added in a medium with the non-solubilized quinone, where was observed a gradual increase in the peak current of reduction and oxidation, until system saturation, indicating phase transfer. Spectroscopic studies of UV-vis have shown the formation of the complex from changes in the absorption band of the βLP and FTIR indicated that the interaction between these compounds probably occurs through the carbonyl groups of the quinone with the amide groups inside the dendrimer.